Associazionismo ateista e accesso all’Intesa con lo Stato. Riflessioni a margine della sentenza n. 7068 del 2014 del Tar Lazio (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione nella "Revista Crítica de Derecho Canónico Pluriconfesional", n. 2/2015.SOMMARIO: 1. Introduzione - 2. L’UAAR e il lungo percorso giudiziario verso la richiesta d’Intesa: l’approdo della sentenza n. 7068 del 2014 del Tar Lazio - 3. Associazionismo ateistico e confessioni religiose: la difficoltà dell’inserimento in una categoria inflazionata - 4. Conclusioni.ABSTRACTThe attention given by the constituent Assembly to the individual and associated way of enjoying the religious freedom, in the logic of protection of the spiritual interests of the human person, should be such as to promote, as a natural consequence of this basic structure of the Constitution, a balanced system in relation to the official contacts between the State and the religious denominations. However, there is the fact of public policies excessively benevolent towards some religious denominations, which causes damage to the affirmation of equal freedom for all individuals, regardless of their cultural orientation, religious or non-religious it is. With the visible manifestation of the atheism (in a public and associated way), doctrine and jurisprudence are called to identify the most appropriate forms of legal protection for some specific group experiences, related, in any case, in the broadest sense, to the religious and spiritual dimension of human life. KEYWORDS: Ateismo; libertà religiosa; legislazione bilateralmente convenuta.Atheism; freedom of religion; bilaterally agreed legislation.